Islamic Educational Psychology Based on a Qur’anic Approach to Shaping the Moral Character of Generation Z in the Digital Era - Safrida Hafni; M. Syukri Azwar Lubis; Khairuddin Lubis (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
This study examines the role of Islamic Educational Psychology in shaping children’s character in the digital era. The study employs a qualitative library research approach by analyzing scholarly literature on Islamic Educational Psychology, character education, child development, Islamic moral values, emotional development, and digital education. Data were collected through systematic identification, selection, and documentation of relevant literature and analyzed using descriptive and thematic analysis. The findings indicate that Islamic Educational Psychology provides an integrative framework for character formation by connecting psychological development with spiritual and moral values. The concept of fitrah positions children as possessing innate potential for goodness that requires appropriate educational guidance and environmental support. Character development is strengthened through the integration of moral knowing, moral feeling, and moral action, supported by exemplary conduct, habituation, emotional regulation, and developmentally appropriate learning. In the digital era, character education must also address ethical technology use, digital responsibility, self-regulation, and critical engagement with information. The study concludes that Islamic Educational Psychology offers a relevant and holistic framework for developing morally resilient, spiritually grounded, emotionally mature, and ethically responsible children